2002
DOI: 10.1159/000064015
|View full text |Cite
|
Sign up to set email alerts
|

Harm Reduction – A Treatment Approach for Resistant Smokers with Tobacco-Related Symptoms

Abstract: Smokers with chronic obstructive pulmonary disease (COPD) appear to represent a hard-core group, and this presents a dilemma for chest physicians. A reduction in cigarette smoking benefits health, and nicotine replacement therapy (NRT) can aid smoking reduction. Hence we studied the efficacy of nicotine gum in helping hard-core smokers with severe COPD to quit. Seventeen smokers with severe COPD (FEV1 38–47% of predicted normal) who smoked >30 cigarettes/day but were unable to quit were encouraged t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 12 publications
(11 reference statements)
1
25
0
4
Order By: Relevance
“…Nicotine replacement therapy (NRT) trials-We located 19 trials that tested NRT for reduction in smokers not currently trying to quit whose data could be aggregated (Table 3) (Rennard et al 1990(Rennard et al ,1994Fager-strom et al 1997;Bolliger et al 2000;Hurt et al 2000;Fagerstrom, Hughes & Callas 2002;Jimenez-Ruiz et al 2002;Kralikova, Kozak & Rasmussen 2002;Rennard et al 2002;Stein et al 2002;Carpenter, Hughes & Keely 2003;Haustein et al 2003;Landfeldt et al 2003;Wennike et al 2003;Carpenter et al 2004;Etter, Laszlo & Perneger 2004;Hecht et al 2004;Joseph et al 2004;Kotlyar et al 2004). None of the trials stated that those in the reduction group were instructed not to quit and many trials stated explicitly that those in the reduction group were encouraged to quit at any point during reduction.…”
Section: Aim 3: To What Extent Can Smokers Substantially Reduce and Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotine replacement therapy (NRT) trials-We located 19 trials that tested NRT for reduction in smokers not currently trying to quit whose data could be aggregated (Table 3) (Rennard et al 1990(Rennard et al ,1994Fager-strom et al 1997;Bolliger et al 2000;Hurt et al 2000;Fagerstrom, Hughes & Callas 2002;Jimenez-Ruiz et al 2002;Kralikova, Kozak & Rasmussen 2002;Rennard et al 2002;Stein et al 2002;Carpenter, Hughes & Keely 2003;Haustein et al 2003;Landfeldt et al 2003;Wennike et al 2003;Carpenter et al 2004;Etter, Laszlo & Perneger 2004;Hecht et al 2004;Joseph et al 2004;Kotlyar et al 2004). None of the trials stated that those in the reduction group were instructed not to quit and many trials stated explicitly that those in the reduction group were encouraged to quit at any point during reduction.…”
Section: Aim 3: To What Extent Can Smokers Substantially Reduce and Mmentioning
confidence: 99%
“…Since that review, several reviews of reduced smoking have appeared (Kozlowski et al 2001;Zellweger 2001;Fager-strom 2002;Jimenez-Ruiz et al 2002;Tonnesen, in press). However, these reviews were brief and did not include more recent reduction studies.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by JIMENEZ-RUIZ et al [18] five out of 12 severe COPD patients demonstrated improvement in respiratory symptoms and pulmonary function after reducing smoking from .30 cigarettes?day -1 to an average of 6 cigarettes?day -1 , with the aid of nicotine replacement therapy. An association has also been demonstrated between nicotine gum use and smoking reduction in both the Lung Health Study [19] and a report by WENNIKE et al [20].…”
Section: Discussionmentioning
confidence: 99%
“…Compensatory changes in smoking behaviour following smoking reduction can be attenuated by nicotine replacement therapy or pharmacological aids that reduce nicotine craving, such as bupropion [17,18]. In a study conducted by JIMENEZ-RUIZ et al [18] five out of 12 severe COPD patients demonstrated improvement in respiratory symptoms and pulmonary function after reducing smoking from .30 cigarettes?day -1 to an average of 6 cigarettes?day -1 , with the aid of nicotine replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation